A novel route of mixed catalysis for production fatty acid methyl esters from potential seed oils sources - Perveen, Shazia; Hanif, Muhammad Asif; Nadeem, Razyia; Rashid, Umer; Azeem, Muhammad Waqar; Zubair, Muhammad; Nisar, Numrah; Alharthi, Fahad A.; Moser, Bryan R. (Multidisciplinary Digital Publishing Institute, 2021)
Depleting petroleum resources coupled with the environmental consequences of fossil fuel combustion have led to the search for renewable alternatives, such as biodiesel. In this study, sunflower (Helianthus annus), mustard (Brassica compestres) and pearl millet (Pennisetum americanum) seed oils were converted into biodiesel (fatty acid methyl esters) by acid-, base- and lipase-catalyzed transesterification, and the resultant fuel properties were determined. The methyl esters displayed superior iodine values (102–139), low densities, and a high cetane number (CN). The highest yield of biodiesel was obtained from mustard seed oil, which provided cloud (CP) and pour (PP) points of −3.5 and 5 °C, respectively, and a CN of 53. The sunflower seed oil methyl esters had a density of 0.81–0.86 kg/L at 16 °C, CP of 2 °C, PP of −8 °C, and a CN of 47. The pearl millet seed oil methyl esters yielded a density 0.87–0.89 kg/L, CP and PP of 4 °C and −5 °C, respectively, and a CN of 46. The major fatty acids identified in the sunflower, mustard, and pearl millet seed oils were linolenic (49.2%), oleic acid (82.2%), and linoleic acid (73.9%), respectively. The present study reports biodiesel with ideal values of CP and PP, to extend the use of biodiesel at the commercial level.